Synthesis and characterization of three amino-functionalized metal–organic frameworks based on the 2-aminoterephthalic ligand1. Issue 17 (7th May 2015) - Yang, Ying; Lin, Rijia; Ge, Lei; Hou, Lei; Bernhardt, Paul; Rufford, Thomas E.; Wang, Shaobin; Rudolph, Victor; Wang, Yaoyu; Zhu, Zhonghua
<x xml:space="preserve">Abstract</x> Three new amino-functionalized MOFs based on 2-aminoterephthalic acid with Mg(ii), Co(ii) and Sr(ii) ions.